C51 SAFETY AND EFFICACY OF DIRECT ORAL ANTICOAGULANTS IN PATIENTS WITH ATRIAL FIBRILLATION ON CONCOMITANT TREATMENT WITH DRONEDARONE. (18th May 2022) - Vio, R; China, P; Marras, E; Cutolo, A; Valle, R; Grassi, G; Saccà, S; Chinellato, A; Themistoclakis, S
Abstract: Background: The use of direct oral anticoagulants (DOACs) in patients with atrial fibrillation (AF) is associated with bleedings. Interactions with dronedarone may increase this risk, but data on concomitant treatment of DOACs with dronedarone are limited. Aim: The primary endpoint was to compare the survival free from the composite endpoint of clinically relevant bleeding, thromboembolic event and death, between AF patients on treatment with dronedarone and different DOACs. The secondary endpoints were to compare the survival free from i) clinically relevant bleeding and ii) clinically relevant major bleeding. Methods: A retrospective study was conducted at the Local Health Unit "Ulss3 Serenissima" of Venice, Italy, from January 1st 2016 to December 31st 2020. The eligible population included AF patients with concomitant prescriptions of DOACs and dronedarone. Patients were divided in 4 groups (rivaroxaban, apixaban, edoxaban, dabigatran). Results: 165 patients were included: 46/165 (28%) on rivaroxaban, 66/165 (40%) on apixaban, 45/165 (27%) on edoxaban, and 8/165 (5%) on dabigatran (Fig.1 ). Over a median follow–up of 339 days, 14/165 (8%) met the primary composite endpoint: 8/165 (5%) had clinically relevant bleedings, of which 1/165 (0.6%) was a clinically relevant major bleeding, 2/165 (1%) had TIAs, and 5/165 (3%) died. We found no difference in survival free from the primary composite endpoint and from clinically relevant bleeding between groups (log–rank test p = 0.19 and p = 0.69, respectively) (Fig. 2A–B ). However, survival free from clinically relevant major bleeding was significantly lower in dabigatran users (p = 0.003) (Fig. 2C ). At a secondary analysis, DOACs contraindicated by 2015 EHRA guide (dabigatran, edoxaban 60 mg), and not by 2018/2021 EHRA guides (rivaroxaban, dabigatran, edoxaban 60 mg), were associated with lower survival from either clinically relevant bleeding or clinically relevant major bleeding (log–rank test p = 0.03 and p < 0.001, respectively) (Fig. 3 ). Conclusions: In our study, there was no difference in survival free from the primary composite endpoint and from clinically relevant bleeding between groups of coadministration. However, survival free from clinically relevant major bleeding was significantly lower in dabigatran users. DOACs contraindicated by 2015 EHRA guide (and not by the latest 2018/2021 EHRA guides) are associated with lower survival from either clinically relevant bleeding or clinically relevant major bleeding.